Anxiety of parents and children in dental care - VIANA FILHO,José Maria Chagas (2018)
ABSTRACT Objective: To verify the prevalence and association of parents’ and children’s anxiety concerning socioeconomic variables and child’s behavior during dental care. Methods: This was a quantitative, observational, transversal and descriptive study. Data collection was performed through a questionnaire aiming at sociodemographic data and dental experience as well as Venham Picture Test, Corah Dental Anxiety Scales and Frankl Anxiety Scale. Data were analyzed using descriptive and inferential statistics (Chi-square and Fisher’s exact test), α = 0.05. Results: The sample consisted of 7 to 9 year- old children (57.9%.), of whom 72.6% were submitted to invasive procedures. The prevalence of anxiety among children was 43.2% (n = 41). Regarding parents / guardians, the prevalence of anxiety was 88.4% (n = 84). A significant association was found between the dental appointment experience and the child’s anxiety (p = 0.050) using the VPT. A significant association between anxiety and the type of dental procedure (p = 0.017) as well as the child’s experience (p = 0.000) using the Frankl scale. Conclusion: There was no association between anxiety and socioeconomic variables. In the variables related to dental experiences, a significant association was found between the experience of the dental appointment and the anxiety of the child using the VPT scale. An association between anxiety and the type of procedure was observed, as well as dental appointment experience, using Frankl scale.